Pelatihan Diversifikasi Produk Madu di Kecamatan Pasirjambu, Kabupaten Bandung, Jawa Barat melalui Kolaborasi Luar Negeri dengan Thammasat University - Taufik Muhammad Fakih; Lina Jamilah; Liza Dzulhijjah; Adryan Fristiohady; Aulia Fikri Hidayat; Budi Prabowo Soewondo; Gita Cahya Eka Darma; Rizki Nuzulfikri; Faqih Radina; Robby Prayitno (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
The main problems found in the Malaya Farmer Group in Pasirjambu District which are partners, are problems related to honey bee harvesting techniques and the diversification of honey products. Some of the methods applied to achieve the target are coordination with domestic and foreign partners through outreach, discussions, identification of problem solutions, selection of alternative solutions to problems, and formulation of implementation stages. Then the implementation of training on honey bee harvesting techniques, the practice of making diversified honey products, and marketing the results of diversified honey products. The achievement of this community service has obtained data in the form of honey product diversification including Honey Combination Soap, Honey Ginger Candy, and Honey Milk Coffee Drinks with the MAZALI brand. In addition, through this community service, training on honey bee harvesting techniques was successfully carried out with the title Trigona Honey Bee Cultivation Training with the theme of Harvesting Techniques, Quality Assessment, and Diversification of Trigona Honey Products. It is hoped that this community service can provide benefits for the development of science, especially in order to help improve skills in honey bee harvesting techniques and develop various diversifications of honey products so that they can become superior in Pasirjambu District.